Study of the effect of the spherical shell angle on the buckling coefficient values - الحايك علي; أكرم صقور (Latakia University Journal -Engineering Sciences Series, 2024)
Among the most prominent structural structures that can be used in public buildings are shells, as they allow the designer to reach large dimensions, and the spherical shell is one of these structures. Through this research, the effect of changing the shell angle on the buckling coefficient in the spherical shell was studied, as four types of angles were studied for (30,45,60,90) different thicknesses (8,10,12) cm and with the effect of dead and live loads on the surface of the shell and with two types of reliable and detailed support. It was found that the buckling coefficient is inversely proportional to the angle of the shell. For the two cases of support, the thickness of the shell is inversely proportional to The buckling coefficient for the same angle. The largest drop in the buckling coefficient values ​​in the case of reliable support between the two angles is (60,90). The similarity in the buckling shapes for the same angle cannot be generalized, and the shape of the buckling differs depending on the angle.